Risk Management in Software Product Lines: An Expert Opinion Survey - Lobato, Luanna Lopes; Machado, Ivan do Carmo; Silveira Neto, Paulo Anselmo da Mota; Bittar, Thiago Jabur; de Almeida, Eduardo Santana; Meira, Sílvio Romero de Lemos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2013: Anais do XII Simpósio Brasileiro de Qualidade de Software, 2013)
Software Product Line (SPL) Engineering is a software development paradigm focused on systematic reuse, which provides companies with several benefits, such as improved quality of delivered products and reduced time to market. However, major investments and considerable risks are also inherent. In this context, managing the risks and providing strategies to avoid and mitigate them are mandatory tasks during software development. In this study, we present the results of an expert survey, carried out with the aim to figure out how the SPL experts have been worked with Risk Management (RM) in their projects. We observed that experts do not always address the RM activities during real world project development, what can be justified that RM is an open issue when related to SPL.